Pengaruh Pendapatan Asli Daerah Dan Dana Perimbangan Terhadap Belanja Modal Dan Tingkat Kemandirian Keuangan Daerah - Wike Nurliza Arpani; Halmawati Halmawati (Jurnal Eksplorasi Akuntansi, 2020)
This study aims to determine the effect of regional original income and balance funds on capital expenditure and the level of local financial independence in district and city governments in Riau Province. The population in this study were all districts and cities in Riau Province from 2010-2018. The sample in this study is a total sampling technique, where the entire population is sampled. The number of districts and cities in Riau Province is 12 districts and cities. analysis conducted using Structural Equation Modeling (SEM). the results of this study indicate that regional own-source revenue and balancing funds have a significant effect on the level of regional financial independence while capital expenditure is not proven to mediate the relationship between regional own-source revenue and the balancing fund with the level of regional financial independence.